EVALUASI DAN PEMODELAN SISTEM DRANASE MENGGUNAKAN PROGRAM EPA SWMM 5.1 DI JALAN AH. NASUTION KOTA TASIKMALAYA - Pratiwi, Fina; Sumarno, Wahyu; Defiana, Yanti (Universitas Majalengka, 2022)
Tasikmalaya is a city that has problems with drainage channels. The location of area from this city that is often to a flood point is AH Nasution Street, Mangkubumi. The largest height of the flood is 50 cm with longest duration of flooding after the flood is started . The purpose of this research is to find out condition of the drainage channel of AH Nasution Street, Mangkubumi, length of drainage is 800 m. The study research using EPA SWMM 5.1 and to find the effective drainage to deal with frequent floods. The results of this research can be concluded that the condition of the channel on AH. Nasution street needs to be repaired, the drainage of this channels is overflow. After the simulation running there are 12 drainage channels that experience overflow and the the largest discharge is at the point of the outfalls 2 (SP.2) with 0.850 m3 / sec. On the channel of drainage AH Nasution Street was calculate to redesigned 2 types of drainage. The typical dimensions with calculation results formula is b = 1 m and H = 1.07 m and the outfalls drainage channel is b = 1 m and H = 1.33 m.